Northern lullaby - Carlstrom, Nancy White; Dillon, Leo; Dillon, Diane (New York : Philomel Books, 1992)
A child says goodnight to the natural world and all those that occupy it.
School Library Journal
Booklist starred
Publisher's Weekly
3.5
K-3
Keywords: Lullabies, American; Children's poetry, American; Bedtime -- Poetry; Nature -- Poetry; Lullabies; American poetry; Bedtime -- Poetry; Nature -- Poetry; Lullabies; American poetry